Theophany and Chaoskampf: the interpretation of theophanic imagery in the Baal epic, Isaiah, and the Twelve - Ortlund, Eric Nels (Gorgias Ugaritic studies, 2010)
Metaphor and myth as competing frameworks for interpreting theophanic imagery -- Thunder and theophany in the Baal epic -- Theophany and chaoskampf in the Book of Isaiah -- Theophany and chaoskampf in the Book of the Twelve -- Metaphor and myth in theophany : borderline cases -- Summary of the argument and conclusions